2010
DOI: 10.1111/j.1651-2227.2009.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IGF1 are a useful predictor of retinopathy of prematurity

Abstract: Determination of IGF1 serum levels in the 3rd week post-partum, independent of gestational age at birth, provides a sufficient and reliable prognostic tool and allows the identification of a group of patients at high risk of developing the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 32 publications
(26 reference statements)
3
59
0
7
Order By: Relevance
“…Pèrez et al (20) showed that low IGF-1 levels were a risk factor in terms of the development of ROP independent of gestational week and increased IGF-1 levels were related with regression of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Pèrez et al (20) showed that low IGF-1 levels were a risk factor in terms of the development of ROP independent of gestational week and increased IGF-1 levels were related with regression of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Perez ve ark. 4 17 Ülkemizde 405 prematüre bebek ile yapılan bir çalışmada da mekanik ventilasyon ile oksijen tedavisi verilen prematür bebeklerde PR riskinin arttığı gösterilmiştir. 18 Term bebeklerde doğumdan sonra ilk haftalarda serum VEGF düzeyleri 200-450 pg/ml arasında değişir ve sonraki aylarda erişkin düzeylerine (10-110 pg/ml) ulaşır.…”
Section: Discussionunclassified
“…1 Son dönemde yapılan çalışmalar PR'nin patogenezinde insulin benzeri büyüme faktörü-1 (IGF-1), eritropoetin (EPO) ve vasküler endotelyel büyüme faktörü (VEGF) gibi faktörlerin önemini göstermektedir. [2][3][4] Vasküler endotelyel büyüme faktörü normal vasküler gelişim için gerekli bir ajandır. Prematüre bebeklere akciğer olgunlaşması yetersizliği dolayısıyla verilen oksijen tedavisi VEGF seviyelerini baskılamaktadır.…”
Section: Introductionunclassified
“…IGF-I exerts its protective actions also in central nervous system and cardiomyocytes (Sun et al, 2010). In premature babies a small concentration of IGF-I is a risk factor of retinopathy of prematurity (Pérez-Muñuzuri et al, 2010). IGF-I deficiency after birth may play a role in development and deterioration of neurological deficiencies in premature babies (Lofqvist et al, 2006).…”
Section: Insulin Like Growth Factor (Igf-i)mentioning
confidence: 99%